Development of a Novel Orthogonal Double Gradient for High‐Throughput Screening of Mesenchymal Stem Cells–Materials Interaction. Issue 18 (4th July 2018) - Zhou, Qihui; Ge, Lu; Guimarães, Carlos F.; Kühn, Philipp T.; Yang, Liangliang; van Rijn, Patrick
Abstract: Surface gradients provide a powerful platform to accelerate multiscale design by efficiently studying of material–cell interactions to ultimately enhance function of synthetic clinical biomaterials. Herein, a novel orthogonal double gradient is reported in which surface stiffness and wettability vary independently and continuously in perpendicular directions, providing unique combinations of stiffness and wettability over a broad range (stiffness: 6–89 MPa; water contact angle: 29°–90°). It is found that mesenchymal stem cell behavior is nonlinearly regulated by surface stiffness and wettability. These combined stiffness and wettability properties of a material significantly affect stem cell adhesion, spreading, nucleus size, and vinculin expression. This high‐throughput screening system enables elucidation of the relationships between biointerface properties and biological behavior, and thereby serves a potential tool for accelerating the development of high‐performance biomaterials. Abstract : Orthogonal stiffness and wettability gradients within a single substrate are developed for elucidating combined physical parameter influences on stem cell behavior and thereby gaining insights in desired cellular responses. Cell behavior is nonlinearly regulated by surface stiffness and wettability. The optimal combined properties for promoting cell adhesion, nucleus size, and vinculin expression are identified based on the orthogonal double gradients.